Dampak Penggunaan Modul terhadap Peningkatan Pengetahuan dan Ketrampilan Keluarga dalam Mestimulasi Tumbuh Kembang Bayi - Wijayanti, Rahayu; Purwandari, Haryatiningsih (Jurusan Keperawatan FIKES UNSOED, 2006)
The aim of the study was to explore the impact of using baby’s growth and developmental module to increase family’s knowledge and skills to stimulate baby’s growth and development at puskesmas Kalibagor Banyumas regency. This study was performed at Puskesmas Kalibagor Kabupaten Banyumas Quasi experimental with two groups pre-post test design was used in this research. Respondents were divided into two groups. Eighteen persons were selected as group intervention and the last seventeen respondents as control group. Research sample was taken by quota sampling method. Research was conducted since September to November 2006. Paired t test found p value at 0.003 and 0.126 on stimulation knowledge and stimulation skill respectively. Furthermore, analysing on control group found p value at 0.031 and 0.107 on stimulating knowledge and skill respectively. Two group analyses utilized T independent sample test was not found significant different between intervention and control group p value at 0.164. Meanwhile, there were no significant differences between intervention and control group in relation to baby’s skills at p 0.952. This research was known, there aren’t different using baby’s growth and developmental module to increase family’s knowledge and skills to stimulate baby’s growth and development between intervention or controll group.